A Morse lemma for degenerate critical points with low differentiability. (2000) - de Moura, Adriano A.; de Souza, Fausto M.
Abstract : We prove a Morse type lemma for, possibly degenerate, critical points of aC 1 function twice strongly differentiable at those points, which allows us to recover, for Finsler metrics, the theorem of Gromoll and Meyer on the existence of infinitely many closed geodesics.